Nationality Education Based on Literary Works Case Studies of 19th-Century Indonesian Modern Literature - Saifur Rohman (MASI Mandiri Edukasi, 2023)
The learning of Indonesian nationality has been focused on understanding the formality of values in ideology, state forms, or forms of government without looking at the lower-layer network consisting of individuals who interact with each other, build events, and form stories, through language. This review is based on Ben Anderson's conception of the nation as an imagined community. Through the object of study of modern Indonesian literature of the 19th century, the nationality that was discovered was not to reinforce the stigma that already existed but instead wanted to prove that the idea of nationality was so fluid, dynamic, and always open to being reinterpreted. The objects of study were Sair Kadatangan Sri Maharaja Siam in Betawi (1870), Sair Jalan Kreta Api (1890) by Tan Teng Kie, Sair from Hal Datangja Poetra Makoeta Keradjaan Roes in Betawi (1891), Sair Kembang (1898), and Njai Dasima (1900). The study uses the semiotic method to offer a single national learning model through literary works. Because, more than just expressing the idea that